Entropy numbers of embeddings of function spaces with Muckenhoupt weights, III. Some limiting cases - Dorothee D. Haroske; Leszek Skrzypczak (Journal of Function Spaces and Applications)
We study compact embeddings for weighted spaces of Besov and Triebel-Lizorkin type where the weight belongs to some Muckenhoupt Ap class. This extends our previous results [25] to more general weights of logarithmically disturbed polynomial growth, both near some singular point and at infinity. We obtain sharp asymptotic estimates for the entropy numbers of this embedding. Essential tools are a discretisation in terms of wavelet bases, as well as a refined study of associated embeddings in sequence spaces and interpolation arguments in endpoint situations.